Treatment adherence and associated factors among glaucoma patients attending Ophthalmic units of referral hospitals in North West Ethiopia, 2019 - Birhanie, Setarg Ayenew; Getie, Girma Alem; Tesfa, Mulugeta; Mulugeta, Henok; Gedfew, Mihretie; Mekete, Yeshimareg Shita; Liknaw, Tiliksew; Teshale, Mikiyas Muche; Tilahun, Melkamu; Amlak, Baye Tsegaye; Yitayew, Fentahun Minwuyelet; Ayenew, Temesgen; et al. (Frontiers in Ophthalmology, 2022)
Objective: Glaucoma is one of the common eye disorders resulting from optic neuropathy, which leads to irreversible blindness if left untreated. Poor adherence to glaucoma medical treatments typically leads to some serious consequences, such as progressive visual impairment and blindness. The aim of this study was to assess adherence to treatment and associated factors among patients with glaucoma attending at Northwest Ethiopia referral hospitals. Method: From March 1st to April 30th, 2019, an institution-based cross-sectional study was conducted on 414 consecutive glaucoma patients attending at Northwest Ethiopia referral hospitals. Data about adherence to glaucoma treatment was collected by using a standardized tool, the Morisky Medication Adherence Scale-8, through an interviewer-administered questionnaire. Each collected data set was coded and entered into Epi-Data version 4.2, and analysis was done by using STATA version 14.0 statistical software. A logistic regression model was fitted to assess the effect of an independent variable on the dependent variable. A p-value < 0.05 was considered to declare a statistically significant association. The study proposal was approved by the Debre Markos University ethical review committee. Results: Among the study participants, 189 (49.5%) were adherent to glaucoma treatment. In this study, occupation (farmer), good knowledge, favorable attitude, a short distance from patients’ homes to hospitals, and scheduling problems for glaucoma medical follow-up visits were significant factors associated with adherence to glaucoma treatments. Conclusion: The study has identified the adherence level as being low. Patient related factors and health care system related factors were significantly associated with adherence to glaucoma treatments. Appropriate patient education and planning a patient follow-up strategy might improve patients’ adherence to glaucoma treatment. Care providers should place emphasis on the importance of adherence.